Prognostic value of right ventricular dilatation in patients with low-risk pulmonary embolism. Issue 6 (14th December 2017) - Côté, Benoit; Jiménez, David; Planquette, Benjamin; Roche, Anne; Marey, Jonathan; Pastré, Jean; Meyer, Guy; Sanchez, Olivier
The prognosis of multidetector computed tomography (MDCT) assessed right ventricular dilatation (RVD) is unclear in patients with pulmonary embolism (PE) and a simplified Pulmonary Embolism Severity Index (sPESI) of 0. We investigated in these patients whether MDCT-assessed RVD, defined by a right to left ventricular ratio (RV/LV) ≥0.9 or ≥1.0, is associated with worse outcomes. We combined data from three prospective cohorts of patients with PE. The main study outcome was the composite of 30-day all-cause mortality, haemodynamic collapse or recurrent PE in patients with sPESI of 0. Among 779 patients with a sPESI 0, 420 (54%) and 299 (38%) had a RV/LV ≥0.9 and ≥1.0 respectively. No difference in primary outcome was observed, 0.95% (95% CI 0.31–2.59) versus 0.56% (95% CI 0.10–2.22; p=0.692) and 1.34% (95% CI 0.43–3.62) versus 0.42% (95% CI 0.07–1.67; p=0.211) with RV/LV ≥0.9 and ≥1.0 respectively. Increasing the RV/LV threshold to ≥1.1, the outcome occurred more often in patients with RVD (2.12%, 95% CI 0.68–5.68 versus 0.34%, 95% CI 0.06–1.36; p=0.033). MDCT RV/LV ratio of ≥0.9 and ≥1.0 in sPESI 0 patients is frequent but not associated with a worse prognosis but higher cut-off values might be associated with worse outcome in these patients. In PE patients with sPESI 0, MDCT RV/LV ≥0.9 and ≥1.0 are not associated with worse prognosis but higher cut-off values might be http://ow.ly/Jda730guiFz